Emerging Sociolinguistic Teaching Trends of English as a First Language in Nigeria - Uwen, God’sgift Ogban; Bassey, Victor Offiong; Nta, Eno Grace (Universitas Negeri Makassar, 2020)
This paper seeks to examine the emerging sociolinguistic trends in Nigeria with the view to ascertaining the use of English as a first language among its speakers particular in Calabar, Nigeria. The study adopts Vygotsky’s (1978) Social Interactionist Theory. The theory is relevant because it accounts for the intentional and changing linguistic attitudes of children believed to be influenced by their early exposure to English as the language spoken by adults and peers within their immediate environment. Data for the study were generated through primary sources, particularly by means of participant observation and administration of questionnaire. Using random sampling technique, 468 questionnaires were distributed to children within the school age bracket of 06 - 13 in 10 selected Private Primary and Junior Secondary Schools in Calabar. With the aid of 20 trained research assistants who are bi/multilinguals in some Nigerian indigenous languages and English, 400 questionnaires filled under supervision were retrieved from the respondents from where the data were extracted and collated for analysis. Findings indicate that 37 percent of the pupils/students are monolinguals who speak only English as their ‘first and native language’. Similarly, 32.5 percent of the target population understand their mother tongue(s) while 30.8 percent of affirm that they speak the indigenous language(s) fluently. Also, it is observed that a total of 63 percent are bi/multilinguals in their mother tongue(s) and English language and could switch or mix codes. The reasons for the increasing preference towards English language, the researchers have observed, range from the persuasive influence from parents, teachers and peers, and the consequences of globalization in addition to the multiple domains of use of English language. This trending communication practice would continue to increase the growing population of English speakers in Nigeria while the indigenous are further endangered.